Place of death among individuals with chronic respiratory diseases in China: Trends and associated factors between 2014 and 2020 - Tong, Xunliang; Wang, Wei; Zhang, Xinyue; Yin, Peng; Gong, Enying; Li, Yanming; Zhou, Maigeng (Frontiers in Public Health, 2023)
Background: Chronic respiratory disease (CRD) is a common cause of mortality in China, but little is known about the place of death (POD) among individuals with CRD. Methods: Information about CRD-caused deaths were obtained from the National Mortality Surveillance System (NMSS) in China. Both individual-level and provincial level characteristics were measured. Multilevel logistic regression models were built to evaluate correlates of hospital CRD deaths. Results: From 2014 to 2020, a total of 1,109,895 individuals who died from CRD were collected by NMSS in China, among which home was the most common POD (82.84%), followed by medical and healthcare institutions (14.94%), nursing homes (0.72%), the way to hospitals (0.90%) and unknown places (0.59%). Being male, unmarried, having a higher level of education attainment and retired personnel were associated with increased odds of hospital death. Distribution of POD differed across the provinces and municipalities with different development levels, also presenting differences between urban and rural. Demographics and individual socioeconomic status (SES) explained a proportion of 23.94% of spatial variations at the provincial level. Home deaths are the most common POD (>80%) among patients with COPD and asthma, which are the two major contributors to CRD deaths. Conclusions: Home was the leading POD among CRD patients in China in the study period, therefore, more attention should be emphasized to the allocation of health resources and end-of-life care in the home setting to meet the increasing needs among people with CRD.